Implementation of Practical Religious Skills Assessment in Fiqh Learning on the Topic of Thaharah in the Merdeka Curriculum - Abdah Muhammad Hasan; Ahmad Sukandar (CV. Media Digital Publikasi Indonesia, 2025)
This study examines the implementation of practical Thaharah assessment within the context of the Merdeka Curriculum at the junior secondary school level. Employing a qualitative approach with a comparative case study design, the research was conducted at MTs An-Nur 1 and MTs An-Nur 3 in Malangbong, Garut. Research subjects included Islamic studies teachers, school principals, and relevant instructional and assessment documents. Data were collected through participatory observation, in-depth interviews, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña.The findings reveal that the quality of rubric design and the consistency of assessment implementation play a crucial role in enhancing students’ religious practice skills. MTs An-Nur 1 demonstrated a high level of implementation fidelity, with assessments embedded in routine instruction, immediate feedback, and well-documented student portfolios. In contrast, MTs An-Nur 3 conducted assessments in a more administrative and less reflective manner. The success of assessment practices at MTs An-Nur 1 was supported by internal factors such as teacher competence, a strong religious school culture, instructional leadership, and adequate infrastructure. The study concludes that the effectiveness of authentic assessment in religious education depends on three key components: instrument validity, implementation consistency, and a supportive school ecosystem. These findings highlight the importance of community-based collaboration and instructional leadership in transforming assessment into a formative and character-building process, rather than a mere administrative procedure.